THE INFLUENCE OF GOOD CORPORATE GOVERNANCE (GCG) AND PROFITABILITY ON COMPANY VALUE - Nuha , Hasna; Rusmawati, Zeni; Sari, Tyasha Ayu Melynda (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study aims to test the effect of independent variables on the dependent variable. The independent variables used in this study are Good Corporate Governance (GCG) and Profitability, and the dependent variable is Company Value. Method: The method used in this study is a quantitative method. The population in this study was 32 technology companies listed on the Indonesia Stock Exchange (IDX) in 2021-2023. The sampling technique used in this study was the purposive sampling technique and obtained a sample of 27 companies during the 2021-2023 period with a total sample of 81 financial reports. Hypothesis testing in this study used multiple linear regression analysis with the help of Statistical Package for the Social Sciences (SPSS) version 25 software. Results: In the results of this study, there were extreme data that caused the data to not be normally distributed, so it was necessary to do outlier data. After outlier, the data shows n or the number of samples is 65 from the total initial sample of 81 because 16 of the samples have extreme values or values that are very different from other data so they must be removed from the sample, because by removing data from the sample, the data can return to normal. The results of the study indicate that Good Corporate Governance (GCG) and Profitability do not affect the value of the company. Novelty: This study provides insights into the impact of Good Corporate Governance (GCG) and Profitability on Company Value, highlighting the necessity of data preprocessing through outlier removal to achieve normal distribution.